Does osteofibrous dysplasia progress to adamantinoma and how should they be treated?. (March 2017) - Scholfield, D. W.; Sadozai, Z.; Ghali, C.; Sumathi, V.; Douis, H.; Gaston, L.; Grimer, R. J.; Jeys, L.
Abstract : Aims: The aim of this study was to identify any progression between benign osteofibrous dysplasia (OFD), OFD-like adamantinoma and malignant adamantinoma, and to investigate the rates of local recurrence, metastases and survival, in order to develop treatment algorithms for each. Patients and Methods: A single institution retrospective review of all patients presenting with OFD, OFD-like adamantinoma and adamantinoma between 1973 and 2012 was undertaken. Complete data were available for 73 patients (42 with OFD; ten with an OFD-like adamantinoma and 21 with an adamantinoma). The mean follow-up was 10.3 years (3 to 25) for OFD, 9.2 years (3.0 to 26.3) for OFD-like and 11.6 years (0.25 to 33) for adamantinoma. Results: The mean age at diagnosis for OFD was 13.5 years (1 to 49), 10.5 years (6 to 28) for OFD-like and 34 years (14 to 86) for adamantinoma. A total of 24 of the 42 patients with OFD (57%) have not required any treatment and have been managed with observation. A total of 18 of the 42 patients with OFD underwent surgery, 13 with curettage and five with resection. In all, three patients developed recurrence following curettage (23%) but none following resection. All these patients were cured with further limited surgery. A total of six patients initially diagnosed with OFD were subsequently found to have OFD-like adamantinoma. Of the ten patients initially diagnosed with OFD-like adamantinoma, three (30%) were managed with observation alone and seven underwent surgery, two with curettage and five with resection. Local recurrence arose in two patients, one each after curettage and resection. No patients with either OFD or an OFD-like adamantinoma developed metastases or had progression to adamantinoma. All patients with an adamantinoma were treated by surgery, three with curettage, six with amputation and 12 with excision. In all, two of the three treated with curettage developed local recurrence, requiring further surgery. Late development of both local recurrence and metastases led to a ten year disease specific survival of 93% which had dropped to 39% by 20 years. Conclusion: We found no evidence of progression from OFD to adamantinoma. Conservative management with observation or curettage is often successful for patients with OFD and OFD-like adamantinoma. Resection with clear margins is required for patients with adamantinoma. Late tumour recurrence is not uncommon in adamantinoma and prolonged follow-up should be considered. Cite this article: Bone Joint J 2017;99-B:409–16.